Optogenetic determination of dynamic and cell-type-specific inhibitory reversal potentials - Burman, RJ; Diviney, T; Călin, A; Gothard, G; Jouhanneau, J-SM; Poulet, JFA; Sen, A; Akerman, CJ (Society for Neuroscience, 2024)
The reversal potential refers to the membrane potential at which the net current flow through a channel reverses direction. The reversal potential is determined by transmembrane ion gradients and, in turn, determines how the channel's activity will affect the membrane potential. Traditional investigation into the reversal potential of inhibitory ligand-gated ion channels (EInh) has relied upon the activation of endogenous receptors, such as the GABA-A receptor (GABAAR). There are, however, challenges associated with activating endogenous receptors, including agonist delivery, isolating channel responses, and the effects of receptor saturation and desensitization. Here, we demonstrate the utility of using a light-gated anion channel, stGtACR2, to probe EInh in the rodent brain. Using mice of both sexes, we demonstrate that the properties of this optically activated channel make it a suitable proxy for studying GABAAR receptor-mediated inhibition. We validate this agonist-independent optogenetic strategy in vitro and in vivo and further show how it can accurately capture differences in EInh dynamics following manipulations of endogenous ion fluxes. This allows us to explore distinct resting EInh differences across genetically defined neuronal subpopulations. Using this approach to challenge ion homeostasis mechanisms in neurons, we uncover cell-specific EInhdynamics that are supported by the differential expression of endogenous ion handling mechanisms. Our findings therefore establish an effective optical strategy for revealing novel aspects of inhibitory reversal potentials and thereby expand the repertoire of optogenetics.